The varved succession of Crawford Lake, Milton, Ontario, Canada as a candidate Global boundary Stratotype Section and Point for the Anthropocene series. (April 2023) - McCarthy, Francine MG; Patterson, R. Timothy; Head, Martin J; Riddick, Nicholas L; Cumming, Brian F; Hamilton, Paul B; Pisaric, Michael FJ; Gushulak, A. Cale; Leavitt, Peter R; Lafond, Krysten M; Llew-Williams, Brendan; Marshall, Matthew; et al.
An annually laminated succession in Crawford Lake, Ontario, Canada is proposed for the Global boundary Stratotype Section and Point (GSSP) to define the Anthropocene as a series/epoch with a base dated at 1950 CE. Varve couplets of organic matter capped by calcite precipitated each summer in alkaline surface waters reflect environmental change at global to local scales. Spheroidal carbonaceous particles and nitrogen isotopes record an increase in fossil fuel combustion in the early 1950s, coinciding with early fallout from nuclear and thermonuclear testing – 239+240 Pu and 14 C: 12 C, the latter more than compensating for the effects of old carbon in this dolomitic basin. Rapid industrial expansion in the North American Great Lakes region led to enhanced leaching of terrigenous elements by acid precipitation during the Great Acceleration, and calcite precipitation was reduced, producing thin calcite laminae around the GSSP that is marked by a sharp decline in elm pollen (Dutch Elm disease). The lack of bioturbation in well-oxygenated bottom waters, supported by the absence of fossil pigments from obligately anaerobic purple sulfur bacteria, is attributed to elevated salinities and high alkalinity below the chemocline. This aerobic depositional environment, highly unusual in a meromictic lake, inhibits the mobilization of Pu, the proposed primary stratigraphic guide for the Anthropocene.